Historical Archaeology in the Twenty-First Century : Lessons from Colonial Williamsburg - Gary, Jack; Edwards, Andrew C.; Edwards-Ingram, Ywone, 1961- (Book collections on Project MUSE., 2021)
Using exemplary approaches and methodologies, this volume addresses key concerns in the field such as amplifying voices of the African diaspora, the development of ethically sound inclusive archaeologies, the value of environmental analyses, and the advantages of virtual models. The research highlighted here provides state-of-the-art examples of how historical archaeology can be used to inform, engage, and educate"--